Effects of marathon training on maximal aerobic capacity and running economy in experienced marathon runners - Lee, E. J.; Snyder, E. M.; Lundstrom, C. L. (Journal of Human Sport & Exercise, 2020)
Maximal aerobic capacity (VO2max) and running economy (RE) are markers of running performance. A valid evaluation of RE may occur through allometric scaling of body mass (alloVO2; ml kg-0.66 min-1), energy cost (EC; kcal/kg.km), or percent of VO2max (%VO2max). Little is known about physiological changes that occur in competitive runners over a marathon training cycle. The VDOT score, incorporating VO2max and RE, enables comparison of race performances under different temperature conditions. This study`s purpose was to determine whether VO2max and measures of RE change with marathon training, and to evaluate the relationship between these variables and VDOT. Eight runners (age 34±2 years; marathon <3:00 males, <3:30 females; five females) completed treadmill marathon-intensity-effort (MIE) and VO2max tests at 10 and 1-2 weeks pre-marathon. Body composition (%BF) was determined using hydrostatic weighing. Paired t-tests were used to compare pre- and post-training values. The alpha level for significance was set at 0.05. Body fat decreased from 18.7±1.5% to 16.7±1.6%, VO2max increased from 51.6±2.4 to 63.9±1.1 ml/kg.min, and %VO2max during the MIE decreased from 82.1±2.0 to 72.3±3.2% (p < 0.05 for all). VDOT was significantly associated with alloVO2 (r = -0.779, p = 0.039) but not with VO2max (r = 0.071, p = 0.867). Experienced competitive runners may increase VO2max and decrease %BF after a marathon-specific training cycle. The decrease in %VO2max in a MIE is likely due to a higher VO2max, as other measures of RE did not change significantly. In this cohort, alloVO2 was negatively correlated with race performance.